Navigating Maritime Commerce Histories: Unearthing the Lancang Kuning Legacy: Menggali Sejarah Perdagangan Maritim: Membuka Misteri Warisan Lancang Kuning - La Ode Zarmin; Miftakhuddin Miftakhuddin (Academia Open, 2023)
This study underscores the untapped historical significance of the Lancang Kuning, a Pinisi type sailing ship, in the context of maritime trade within the Nusantara archipelago, and the implications it carries for global maritime historiography. By employing a comprehensive historical research methodology—encompassing heuristics, criticism, interpretation, and historiography—we delve into verbal and object sources, followed by rigorous data triangulation. Our findings unearth that the Lancang Kuning, initially named La Suni, was constructed in 1860 by Laode Ntauale in Katilombu, Sampolawa, and later relocated to Riau in 1865 to bolster trade activities in Tanjung Buton. The ship's creation was necessitated by the need for a vessel capable of large-scale commodity transport beyond the Nusantara region. The ship significantly contributed to the prosperity of the creator's family, its crew, and the local community, with the management entrusted to its crew. However, the ship ceased to operate post Laode Ntauale's demise and was subsequently abandoned in Siak, Riau. This study accentuates the Lancang Kuning's pivotal role in regional trade, offering a nuanced understanding of maritime trade history, vital for global maritime scholars and policymakers. Highlights: Lancang Kuning, a Pinisi type sailing ship built in 1860, played a crucial role in enhancing maritime trade within the Nusantara region. The ship's construction was necessitated by the demand for large-scale commodity transport beyond the Nusantara archipelago. Post the demise of its creator, Laode Ntauale, the ship was abandoned, highlighting the transient nature of maritime trade mechanisms and their dependency on key individuals. Keywords: Buton's maritime culture, maritime history, Lancang Kuning ship, the history of the Butonese people